Development and Application of a High-sensitivity Acoustic Sensor Based on Open Cavity Fabry-Perot Interferometer - Oleg Morozov; Timur Agliullin; Airat Sakhabutdinov; Artem Kuznetsov; Bulat Valeev; Mohammed Qaid; Roman Ponomarev; Danil Nurmuhametov; Anastasia Shmyrova (Science and Technology - Recent Updates and Future Prospects Vol. 6, 2024)
Aims: This study aims to develop a highly sensitive fiber optic hydraulic acoustic sensor utilizing a Fabry-Perot interferometer formed inside an open cavity at the end of an optical fiber, enhancing its potential for precise acoustic measurements in various media. Study Design: The research involves experimental design utilizing optical fiber technologies and interferometry. Place and Duration of Study: Research conducted at the Department of Photonics, Kazan National Research Technical University, Kazan, Russia, from September 2023 to December 2023. Methodology: A macro cavity in the shape of a droplet was engineered at the fiber end using a combination of catastrophic plasma melting and controlled fusion. The end face of the optical fiber, shaped into this macro cavity, was immersed in liquid to form a closed area with gas, where the interface surfaces served as Fabry-Perot mirrors. This setup was utilized to measure the sensitivity of the system to changes in acoustic waves across different frequencies and pressures. Results: The newly developed fiber optic microphone exhibited sensitivity across a broad acoustic frequency range from 1 Hz to 100 kHz. Notably, limiting the interferometer length variation demonstrated a linear change in the reflection coefficient, varying between 0.017 and 0.089, confirming high precision and significant improvement over traditional sensors. Conclusion: The innovative use of an open cavity Fabry-Perot interferometer in fiber optic microphones presents a significant advancement in acoustic sensing technology. This development offers a promising route for enhancing the performance of acoustic sensors used in various scientific and industrial applications. Further studies are recommended to explore the integration of this technology into commercial sensing systems.